LEARNING STYLES RELATIONSHIP TO VALUE GPA CHEMISTRY EDUCATION STUDENTS MULAWARMAN - Abdul Majid (PROSIDING SEMINAR KIMIA, 2015)
The student's learning style is typical of the way a person in performing activities of learning, where learning style is one factor that can affect student cumulative grade point. Therefore, research on "Learning Styles Relationship To Value GPA Chemistry Education Students Mulawarman". This study was aimed to investigate the relationship between the student learning styles of cumulative grade point Mulawarman Chemical Education.The method was used in this research is the descriptive analytic. The samples were Mulawarman chemistry education students cluster random selected as many as 127 students. The data collection was performed by two methods: the questionnaires and interviews.The results of the study were analyzed using product moment correlation test with significance level of 0.05 were performed with SPSS. Which was obtained r = 0.231 (low correlation), thit = 2.81185 and ttab=1.65714 so thit>ttab. Hα means that Ho is rejected and accepted, that there is a significant correlation between learning styles on the value of the